Traditional knowledge in festivals: agricultural practices and biodiversity conservation among the Ho tribe of Jharkhand - Raj, Anand; Dave, Deeksha (Ethnobotany Research and Applications, 2026)
Background: The Ho tribe of Jharkhand weaves ecological knowledge into seasonal festivals that guide agricultural practices and promote biodiversity conservation. These rituals, rooted in tribal cosmology, foster sustainable living and preserve traditional knowledge across generations. Methods: Ethnographic research was carried out in ten villages of West Singhbhum district during two agricultural seasons (February and October 2024). Data collection involved 150 participants through semi-structured interviews, focus group discussions (FGDs), and participant observation. Six major festivals Maghe, Baha, Hero, Hermut, Bartauli, and Jomnama were studied for their connections to seasonal farming and ecological practices. Results: The festivals align with stages of the agricultural cycle, such as seed purification, soil preparation, transplantation, pest control, and harvest. Sacred species like Sal (Shorea robusta) feature prominently across rituals for their spiritual and ecological roles. Over 70% of participants expressed concern about declining knowledge transmission due to youth migration and changing cultural dynamics. Conclusions: The Ho community’s festivals act as cultural mechanisms for agroecological stewardship and biodiversity conservation. Recognizing and supporting these practices is critical amid threats from modernization and environmental change. Policies aligned with SDGs 13 and 15 should incorporate Indigenous Knowledge Systems to foster community-based conservation. Keywords: Ho Tribe, Traditional Knowledge, Biodiversity Conservation, Indigenous Festivals, Oral Traditions